Current topics in membranes. - Benos, Dale J. (Current topics in membranes, 1999)
Sodium reabsorbing epithelia play a major role in whole-body sodium homeostasis. Some examples of sodium regulating tissues include kidney, colon, lung, and sweat ducts. Sodium transport across these membranes is a two-step process: entry through an amiloride-sensitive sodium channel and exit via the ouabain-sensitive sodium/potassium ATPase. The sodium entry channels are the rate-limiting determinant for transport and are regulated by several different hormones. The sodium channels also play a significant role in a number of disease states, like hypertension, edema, drug-induced hyperkalemia, and cystic fibrosis. Amiloride-Sensitive Sodium Channels: Physiology and Functional Diversity provides the first in-depth exchange of ideas concerning these sodium channels, their regulation and involvement in normal and pathophysiological situations. Key Features * Summarizes current state of amiloride-sensitive sodium channel field * Analyzes structure-function of epithelial sodium channels * Discusses immunolocalization of epithelial sodium channels * Examines hormonal regulation of sodium channels * Discusses sodium channels in lymphocytes, kidney, and lung * Considers mechanosensitivity of sodium channels * Provides ideas on sodium channels and disease.